Pelatihan Bina Orang Tua Sebagai Upaya Peningkatan Literasi Perkembangan Anak Usia Dini Kepada Orang Tua - Abdul Aziz, Ahmad; Bahfen, Munifah (Pendidikan Matematika, FKIP Universitas Mataram, 2025)
The stages of child development from infancy to early childhood are crucial moments and require effective stimulation in order to improve the quality of children's lives in the next stage. The early childhood period begins when children are 0-8 years old. For parents to be able to improve their understanding and knowledge regarding parenting patterns in order to optimize child development at an early age. The design in this training uses the Experiential Learning model. The method used in this training is the provision of pre-test and post-test lectures and question-answer panels. Based on the results of the comparative analysis of pre-test and post-test answers, it can be concluded that the Parent Development (BOT) training held this time was able to improve the understanding and knowledge of training participants. A total of 18 out of 21 participants showed significant differences in the answers to the pre-test and post-test results they worked on. The majority of these participants were seen to be able to further elaborate and explain their answers according to the training material that had been given previously. This training requires further in-depth and continuous observation to ensure that there are indeed changes, in this case improvements, to the understanding and knowledge of training participants regarding optimal learning methods applied to early childhood.